Freshwater saga : memoirs of a lifetime of wilderness canoeing in Canada - Morse, Eric W., 1904-1986 (University of Toronto Press, 1987)
At an Ottawa dinner party in 1951 a group of three Canadians and three foreign diplomats planned a canoe trip on the Gatineau River. It was the first of many trips by a group dubbed by the Ottawa press the Voyageurs, whose most enthusiastic member was Eric Morse. Morse loved canoeing. This memoir is a celebration of his ruling passion and the friends who shared it with him. As a boy Morse had found his hunger for wilderness satisfied on Canada's rivers and lakes. As an adult he chose Ottawa to settle in because of its nearness to good canoeing country. There he encountered the congenial souls who would share many of his holidays over the next fifty years. In his lifetime, Eric Morse saw more of Canada's wilderness than most people have dreamt of. He loved the Arctic best. Recalling his expeditions in later life to the far north, he writes vividly of the Thelon, the Kazan, and the paradisiacal Taltson. In tribute to a man who knew well and loved the waters of the north, a river in the Barrens has been officially named after him.